Self-medication prevalence and associated factors among adult population in Northern India: A community-based cross-sectional study - Khushboo Juneja; Ambren Chauhan; Tuhina Shree; Priyanka Roy; Mainak Bardhan; Absar Ahmad; Amit Singh Pawaiya; Ayush Anand (SAGE Open Medicine, 2024)
Objectives: This study aimed to determine self-medication prevalence and its associated factors. Methods: A community-based cross-sectional study was conducted in the urban and rural catchment areas of Uttar Pradesh, India, among 440 adults using a pretested, semistructured questionnaire. The Chi-square test and logistic regression were used to determine the association of self-medication prevalence with various independent variables. The associations were reported as adjusted odds ratios and 95% confidence intervals. Results: The prevalence of medication use was 66.4%. The majority of participants (45%) took medicine for fever, cough (40.1%), and cold (31.8%). Allopathy (83.2%) was the most common medicine system used for self-medication. More than half reported taking medicine such as paracetamol (52%), followed by cough syrup (21%) and antihistaminic (17%). Convenience (46%) and lack of time (35.3%) were commonly cited reasons for self-medication. Also, 64.4% of the respondents practiced self-medication on the pharmacist’s recommendation. Urban participants (adjusted odds ratio: 9.85, 95% confidence interval: 5.32–18.23), females (adjusted odds ratio: 2.32, 95% confidence interval: 1.18–4.57), skilled workers (adjusted odds ratio: 5.62, 95% confidence interval: 1.80–17.5), and those who completed primary school (adjusted odds ratio: 2.48, 95% confidence interval: 1.16–5.25) were more likely to self-medicate than rural, male, unemployed, and illiterate participants, respectively. Also, participants whose income was 30,000 Indian rupees (adjusted odds ratio: 3.21, 95% confidence interval: 1.00–10.21) were more likely to self-medicate than those whose income was less than 4000. Conclusions: A high prevalence of self-medication was found, particularly in urban areas. Convenience and lack of time were commonly cited reasons for self-medication. Allopathy was the most widely used medicine system for self-medication. Antipyretics, cough syrups, and antiallergics were most commonly self-medicated. Gender, education, and income were associated with self-medication. The study highlighted the increased usage among females which could be further explored and role of pharmacists’ recommendation as a major driver for self-medication.